Analisis Kebutuhan Pengguna Lulusan terhadap Kompetensi Lulusan Program Studi Ilmu Perpustakaan dan Informasi Islam Institut Agama Islam Negeri Curup: Indonesia - Marleni, Marleni; Iswanto, Rahmat; Perdana, Moga; Rizkyantha, Okky (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2024)
This study aims to determine the level of user needs for graduates of the Islamic Library and Information Science Study Program, Curup State Islamic Institute, Curup State Islamic Institute, based on general competencies stipulated by the Regulation of the Head of the National Library of the Republic of Indonesia Number 6 of 2016. This study uses quantitative methods. Quantitative data collection in this study used a questionnaire or questionnaire method. Furthermore, the authors use the Likert’s scale as a reference basis for determining the level of need. The results of the data obtained that the competency requirements needed by the school library in Rejang Lebong regarding the ability to carry out library material development management, the ability to carry out library management is needed, the ability to provide library services and the ability to implement library information systems are needed, the ability to carry out the development of the librarian profession, the ability to organize the library materials, and the ability to preserve library collections are also very needed.